Evaluation of the functional performance and technical quality of an Electronic Documentation System of the Nursing Process - de Oliveira, Neurilene Batista (Escola de Enfermagem de Ribeirão Preto / Universidade de São Paulo, 2015)

(untitled) (Rev Lat Am Enfermagem)
OBJECTIVE: To evaluate the functional performance and the technical quality of the Electronic Documentation System of the Nursing Process of the Teaching Hospital of the University of São Paulo. METHOD: exploratory-descriptive study. The Quality Model of regulatory standard 25010 and the Evaluation Process defined under regulatory standard 25040, both of the International Organization for Standardization/International Electrotechnical Commission. The quality characteristics evaluated were: functional suitability, reliability, usability, performance efficiency, compatibility, security, maintainability and portability. The sample was made up of 37 evaluators. RESULTS: in the evaluation of the specialists in information technology, only the characteristic of usability obtained a rate of positive responses of less than 70%. For the nurse lecturers, all the quality characteristics obtained a rate of positive responses of over 70%. The staff nurses of the medical and surgical clinics with experience in using the system) and staff nurses from other units of the hospital and from other health institutions (without experience in using the system) obtained rates of positive responses of more than 70% referent to the functional suitability, usability, and security. However, performance efficiency, reliability and compatibility all obtained rates below the parameter established. CONCLUSION: the software achieved rates of positive responses of over 70% for the majority of the quality characteristics evaluated.